Activated‐Ester‐Type Photocleavable Crosslinker for Preparation of Photodegradable Hydrogels Using a Two‐Component Mixing Reaction. Issue 2 (13th August 2014) - Yanagawa, Fumiki; Sugiura, Shinji; Takagi, Toshiyuki; Sumaru, Kimio; Camci‐Unal, Gulden; Patel, Alpesh; Khademhosseini, Ali; Kanamori, Toshiyuki
<x xml:space="preserve">Abstract</x> Photodegradable hydrogels have emerged as powerful platforms for studying and directing cellular behavior in a spatiotemporally controlled manner. Photodegradable hydrogels have previously been formed by free radical polymerizations, Michael‐type addition reactions, and orthogonal click reactions. Here, an ester‐activated photocleavable crosslinker is presented for preparing photodegradable hydrogels by means of a one‐step mixing reaction between the crosslinker and a biocompatible polymer containing amino moieties (amino‐terminated tetra‐arm poly(ethylene glycol) or gelatin). It is demonstrated that photodegradable hydrogels micropatterned by photolithography can be used to culture cells with high viability and proliferation rates. The resulting micropatterned cell‐laden structures can potentially be used to create 3D biomaterials for various tissue‐engineering applications.